Degradable fibrin hydrogels for transplantation of iPSC-derived retinal pigment epithelial cell monolayers - Marmorstein, Alan D.; Scruggs, Brittni A.; Knudsen, Travis; Hill, Matthew; Kopp, Francesca N.; Trncic, Emma; Korda, David; Atherton, Evan; Berger, Aubrey; Finnemann, Silvia C.; Gandhi, Jarel; Iezzi, Raymond (Frontiers in Cell and Developmental Biology, 2026)
Death or dysfunction of retinal pigment epithelium (RPE) cells occurs in age-related macular degeneration (AMD) and certain inherited retinal dystrophies (IRDs). Induced-pluripotent stem cell (iPSC) derived-RPE have been used in early-stage clinical trials to treat AMD and IRDs by injecting them as a cell suspension or monolayers. While RPE transplant shows therapeutic potential, issues ranging from failure to repopulate the entire treatment area, clumping and monolayer folding, and a foreign body response to the support have been reported. We’ve shown that RPE can be grown on high concentration (>30 mg/mL) degradable fibrin hydrogels, and that cell free fibrin hydrogels implanted in the subretinal space degrade without causing inflammation. Here we describe manufacture and surgical implantation of degradable fibrin hydrogels carrying iPSC-RPE into a porcine model of geographic atrophy (GA). Large (15.25 × 58.42 × 0.2 mm) fibrin gel blanks were produced by injection molding, and iPSC-RPE were grown on their surface. Using a mechanical punch, the blank was subdivided into 1.5 × 5.0 × 0.2 mm doses, which fit a custom tool used for storage and surgical placement. Following aseptic packaging, RPE and gels were stable at 37 °C for at least 7 weeks. When transplanted into a pig model of GA, the fibrin scaffold degraded in <1 month and the iPSC-RPE provided partial rescue from GA as assessed by preservation of photoreceptors and blood flow in the choriocapillaris. We conclude that iPSC-RPE delivered on degradable fibrin hydrogels represent a potentially safe and effective approach to RPE transplantation.